Вкус запретного плода: роман / Ирен Беллоу - Беллоу Ирен (Панорама романов о любви, 2013)
Экземпляры: К.Х. (20200316) / Инвентарный номер: 47748 / Цена: 36.00 / Сис.шифр: И(Англ.) / Авт.знак: Б 43 / ГРНТИ: 17.82 / ББК: 84(4 Вел)